The psychology of terrorism - Shortland, Neil D. (The psychology of everything, 2021)
What is terrorism? Can anyone be radicalized? How can we respond to terrorist acts? The Psychology of Terrorism seeks to explain why some acts of violence are considered terrorism and others are not, and why some individuals may be more susceptible to engaging in radical terrorist behavior. Debunking myths and lazy stereotypes, the book delves into some of the most shocking atrocities of our times to discuss the complex and varied psychological characteristics of individual terrorists, organized groups, and their acts.